Skene's gland duct cysts: The utility of vaginal/transperineal imaging in diagnosis and mapping for surgery - Petrus Kruger; R Kung; F Hamidinia; R Rahmani (South African Medical Association, 2016)
We report three patients with Skene’s gland cysts diagnosed on transvaginal and transperineal 2D and 3D sonography. We demonstrate that pelvic floor imaging is a useful diagnostic tool and aids in preoperative surgical planning. The real-time nature of this form of imaging and the addition of 3D ultrasonography demonstrate internal architecture and spatial relationships of periurethral pathology, thus aiding presurgical mapping. In this case series patients were followed up and results of surgical procedures and histological findings were recorded. Marsupialisation and resection are accepted surgical options in symptomatic Skene’s gland cysts. Usually simple drainage will not suffice for management of a symptomatic Skene’s gland cyst, as demonstrated in one of our cases. Asymptomatic cysts can be followed conservatively.